Digital Storytelling-Based Tasks on Speaking Classroom; Seen from ESL Learners’ Lenses - Fitri, Hilwa Alfiani; Mohamad, Mahani; Harianingsih, Ika; Wadi, Ari Safar (Universitas Islam Negeri Mataram, 2022)
Over the course of a decade, digital storytelling (DST) has earned a growing amount of attention as a strong instructional resource that has grabbed the interest of scholars. Digital storytelling (DST) has emerged as a promising pedagogical approach that could help moderate the usefulness of media in the classroom. Myriad studies have demonstrated the positive effects of digital storytelling (DST) on the students’ language skills; however, these studies rarely include ESL students and their realistic depictions of everyday basis. To address the void, this quantitative study aimed to survey ESL students' point of view of DST-based task on speaking classroom. Relying on Anwar's (2016) TBLT approach instruction, the current study involving thirty-four students studying at Universiti Sultan Zainal Abidin, Malaysia. The statistical evidence indicated ESL students perceive the implementation of digital storytelling-based tasks improves their motivation while allowing them to develop ideas and collaborate among groupmates. Implications and recommendations for future studies are discussed.